Efficiency of application of fungicides against dry spot potatoes - Bogdanovych, S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
In the zone of the Northern Forest-Steppe of Ukraine, the effectiveness of modern fungicides against the dry spotting of potatoes in different maturity varieties has been studied. It has been established that fungicides show a higher protective effect with their preventive application, before the appearance of the first signs of the disease. The highest technical efficiency of the studied varieties was characterized by fungicides of system-contact action Ridomil Gold MC 68WG 2.5 kg/ha and Concento 450 SC, 2.0 l/ha.